2005
DOI: 10.1093/ajcn/82.5.923
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in older adults: technical review and position statement of the American Society for Nutrition and NAASO, The Obesity Society

Abstract: Obesity causes serious medical complications and impairs quality of life. Moreover, in older persons, obesity can exacerbate the age-related decline in physical function and lead to frailty. However, appropriate treatment for obesity in older persons is controversial because of the reduction in relative health risks associated with increasing body mass index and the concern that weight loss could have potential harmful effects in the older population. This joint position statement from the American Society for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
651
3
22

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 805 publications
(701 citation statements)
references
References 184 publications
25
651
3
22
Order By: Relevance
“…Aging can alter body composition, thereby reducing the correlation between increased BMI and excess adiposity (30). Using waist circumference, rather than BMI (or body weight), in an older population would more adequately reflect adiposity (31); however, we did not have 4-y repeated measures of waist circumference in the NHS, NHS II, and HPFS cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Aging can alter body composition, thereby reducing the correlation between increased BMI and excess adiposity (30). Using waist circumference, rather than BMI (or body weight), in an older population would more adequately reflect adiposity (31); however, we did not have 4-y repeated measures of waist circumference in the NHS, NHS II, and HPFS cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent communications or visits may be needed. 67,68 Blood Pressure Control Blood pressure should be measured at each medical visit, and goals and medications reevaluated. Home blood pressure monitoring may be helpful.…”
Section: Glycemic Controlmentioning
confidence: 99%
“…Interestingly, Lang et al demonstrated recently in non-institutionalized men and women aged 65 years or older followed for 5 years that excess body weight had stronger associations with impaired physical function than with mortality (43). The lower effect on mortality of excess body weight in older people than in younger adults might be due at least in part to a survival bias, older obese people being also possibly those who are resilient to some noxious effects of excess body weight (43,44).…”
Section: Independent Predictors Of Mortality In Elderly Womenmentioning
confidence: 99%